(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
each area has its own laws of activity, a tendency to follow, applied technology and approaches. The art field is no exception. As in all types of art, in fine art there are factors, features and parameters that characterize its properties. Modeling fine arts classes allows you to maintain a reasonable balance between theory and practice, organize educational activities. Provides the educational process not only intellectual, but also moral development of children, their independence, activity. Allows students to master the experience of social interaction. Unites students and develops communication skills.